Defining the drinking experience concept: a case study of craft and industrial beer consumption; La experiencia de beber cerveza: definiendo el concepto de consumo experiencial en la cerveza industrial y artesanal - Gómez Corona, Carlos (Universidad Autónoma Metropolitana, 2016)
The are a of stud y of this thesis is sensory and consumer science, with a strong influence of the fi eld of cognitive and social psychology. The thesis focus is on the study of the experience of drinking (consumption experience or product experience). With the objective to contribute to the understanding of food choice processes and consumption of food an d beverages. As well as to develop a tool (methodology) capable of measuring the experience of drinking threw a set of human systems (affects, senses and cognition). The case study used in this thesis to measure the experience of drinking is beer, comparin g through different studies the similarities and differences between craft and industrial beer. Product experience refers to all the effects the product has on consumers, they can be emotional, sensory or cognitive. Although this concept is not new in the fiel d of consumer psychology, it has been less explored in the food and beverage domain. In the past years, the concept of consumer experience and product experience has been used in services (e.g. tourism), material objects (e.g. cell phones). Today we do not know the differences that may exist in the use of the concept of product for material products compared to food and beverages . The thesis throughout five ch apters raises a study of the experience of drinking, more specifically the experience of drinki ng beer. The first chapter has for objective to understand the beer consumer in Mexico in respect to the habits of consumption, attitudes, brands usage more often, and to find a typology of industrial and craft consumers. Additionally, the results of a qua litative study are exposed (consumer ethnographies) to have a deep dive in the motivations towards the consumption of craft beer in the Mexican consumer. The second chapter explores the variables associated to the experience of drinking beer, also via a qu alitative study (contextual focus groups) and put in evidence the differences between the experience of using a material object and the experience of drinking a beverage (or a food). The results of this study show that the experience of drinking beer is re lated to: habits of consumption, attitudes, sensory experience, affective experience (emotional), cognitive experience, shopping, individual vs social consumption and the specific benefits searched by consumption. The third and fourth chapter deepen in the mental and social representation of beer. In first place, the mental representation of beer is perceived differently according to the gender and type of consumption (industrial or craft beer). To access to the mental representation, a sorting task was use d. The results show that women categorize the beers based on their attitudes while men make the categories based on their previous experience or information of the beer. On the other hand, by studying the social representation of beer, using the methodolog y of the social representation from social psychology, it was evidenced the cultural differences existing between the consumers of two countries: Mexico and France. The results manifest that the way in which the representation of the craft beer is made is different between the two countries, having as an axe the description of the beer in France, and hedonics in Mexico . In the case of the French consumers, the representation of the craft beer is shared across industrial and craft consumers, while in Mexico both types of consumers do not share the same representation . Finally, in chapter fi ve the information from the prev ious chapters is condensed into one methodology to measure the drinking experience of beer that can take into consideration the three humans systems: affects, senses and cognition. The study performed in this chapter was done in two basic steps: visual evaluation and product test. The results put forth that it is possible to measure the experience of drinking beer and identify which is the sal ient system or dimension used during the consumption. In the study it was found that the craft beers evoke a more cognitive experience, while industrial beers evoke a more emotional or sensory experience. The thesis concludes with the results of the exper ience measurement, exhibiting the different paths to follow for a better understanding and research on the experience concept, which can be in beverages or foods.; El área de estudio de esta tesis es el análisis sensorial y estudios con consumidores, con una fuerte influencia del campo de la psicología cognitiva y social. La tesis se enfoca en el estudio de la experiencia de consumo , con el objetivo de profundizar en el entendimiento de los proceso s de elección y consumo de alimentos y bebidas, así como desarrollar una herramienta capaz de medir la experiencia de consumo a través de los diferentes sistemas que tiene el ser humano (sensorial, afectivo y cognitivo). El caso de estudio utilizado para medir la ex periencia de consumo es la cerveza, comparando a través de la tesis las relaciones y diferencias que existen entre el consumo de cerveza artesanal e industrial. La experiencia de un producto se refiere a todos los efectos emocionales, sensoriales y cogniti vos que un producto puede tener sobre una persona. Sin embargo, este concepto, aunque no es nuevo en el área de la psicología del consumidor, ha sido poco estudiado con respecto a su relación con alimentos y bebidas. En los últimos treinta años, el concep to de consumo experie ncial, experiencia de producto ha sido utilizado en servicios ( ej. turismo), objetos materiales ( ej. celulares, tasas, etc.). Pero, n o se conoce las diferencias que podrían existir con respecto al consumo de alimento s y bebidas. La tes is a lo largo de cinco capítulos plantea un estudio de la experiencia de consumo de bebidas, más específicamente del consumo de cerveza. El primer capítulo tiene por objetivo conocer al consumidor de cerveza en México con respecto a los hábitos de consumo, actitudes, macas de cerveza que más se consumen y encontrar una tipología de los consumidores. Adicionalmente se profundiza en los resultados de un estudio cualitativo (etnografías con consumidores) para profundizar en las motivaciones , variables involucr adas y actitudes hacia el consumo de cerveza artesanal. El segundo capítulo explora las variables asociadas a la experiencia de tomar cerveza, utilizando un estudio también cualitativo (sesiones de grupo contextuales) y pone en evidencia las diferencias en tre la experiencia de consumo en un objeto material versus una bebida. Los resultados de este estudio muestran que la experiencia de tomar cerveza está relacionada con: los hábitos de consumo, actitudes, la experiencia sensorial, la experiencia afectiva (o emocional), la experiencia cognitiva, la experiencia de compra del producto, el consumo individual versus social, y los beneficios específicos buscados en el consumo de cerveza . El tercer y cuarto capítulo profundiza n en la representación mental y social de la cerveza. En primer lugar, la representación mental de la cerveza es percibida diferente de acuerdo al género y tipo de consumidor (cerveza industrial o artesanal). Para obtener la representación mental se realizó una prueba de categorización ( sortin g task ) en done los resultados muestran que las mujeres categorizan las cervezas basadas en las actitudes hacia la cerveza, mientras que los hombres realizan la categorización basados en su experiencia previa o información sobre las cervezas. Por otro lado , al estudiar la representación social de la cerveza, usando la metodología estructural de las representaciones en psicología social se ponen en evidencia las diferencias culturales que existen en el consumidor en dos países: México y Francia. Los resultad os muestran que la forma en la que se construye la representación es diferente entre países, teniendo como eje la descripción de la cerveza en Francia, y como aspectos hedónicos en el caso del consumidor mexicano . En el caso del consumidor francés , la repr esentación de la cerveza artesanal es más compartida entre consumidores de cerveza industrial y artesanal, mientras que los diferentes tipos de consumidores en México no comparten una misma representación social. Finalmente, el capítulo cinco muestra cómo se utilizó la información de los estudios precedentes de la tesis para diseñar un estudio cuantitativo en donde se midiera la experiencia de tomar cerveza. El estudio constaba de dos condiciones: evaluación visual y prueba de producto. Los resultados muest ran que es posible medir la experiencia de tomar cerveza con base en las dimensiones más relevantes durante el consumo, más afectiva , cognitiva o sensorial. En el estudio se encontró que las cervezas artesanales tienen una experiencia de consumo más cognit iva, mientras que las cervezas industriales son más emocionales y sensoriales. La tesis concluye con los resultados de la medición de la experiencia de consumo en las cervezas y muestra que los caminos para una mayor investigación de l concepto de experien cia pueden ser en alimentos y otras bebidas, con el objetivo de validar el uso del concepto y las variables relacionadas con el mismo.